Analysis of the Effect of School Quality and School Facilities on School Selection Decisions and Their Implications for Student Satisfaction - Said Rahmat Aulia; Irsan; Iskandar (el-Nizami : Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze the effect of school quality and school facilities on school selection decisions and their implications for student satisfaction at MAN 14 Jakarta. The background of this study departs from the increasing competition among educational institutions in attracting new students, which requires schools to improve the quality of services and learning support facilities. School quality and educational facilities are seen as important factors that influence students' perceptions, decisions and satisfaction with the institutions where they pursue education. This study uses an explanatory quantitative approach with the Structural Equation Modeling (SEM) method to explain the causal relationship between research variables. The population in this study were all MAN 14 Jakarta students, with the number of samples determined through proportional random sampling techniques to represent the overall characteristics of the population. Data collection was carried out using an instrument in the form of a questionnaire with a Likert scale, which had been tested for validity and reliability. The variables analyzed include school quality (X₁), school facilities (X₂), school selection decisions (Y₁), and student satisfaction (Y₂). The results showed that school quality has a positive and significant influence on school selection decisions. School facilities are also proven to have a significant effect on students' decision to choose a school. Furthermore, school selection decisions have positive implications for the level of student satisfaction. This confirms that students who choose schools with good quality and facilities tend to have higher satisfaction in the learning process. Overall, this study concludes that improving the quality of educational services and providing adequate learning facilities are important strategies in increasing school attractiveness and creating sustainable learning satisfaction among students.